2014
DOI: 10.18632/aging.100636
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant SkQ1 delays sarcopenia-associated damage of mitochondrial ultrastructure

Abstract: A comparative electron-microscopic study of ultrastructure of mitochondria in skeletal muscles of the 3-and 24-month-old Wistar and OXYS rats revealed age-dependent changes in both general organization of the mitochondrial reticulum and ultrastructure of mitochondria. The most pronounced ultrastructure changes were detected in the OXYS rats suffering from permanent oxidative stress. In the OXYS rats, significant changes in mitochondrial ultrastructure were detected already at the age of 3 months. Among them, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Since neurodegenerative conditions and aging have been associated with chronically elevated levels of ROS, antioxidant treatments have been proposed or are currently in clinical trial [70][71][72]. In our work, we observed that HDAC4mKO mice neither increased the levels of ROS and RNS in skeletal muscle nor induced the expression and activation of the enzymes involved in the antioxidant response, 1 week following denervation.…”
Section: Discussionmentioning
confidence: 53%
“…Since neurodegenerative conditions and aging have been associated with chronically elevated levels of ROS, antioxidant treatments have been proposed or are currently in clinical trial [70][71][72]. In our work, we observed that HDAC4mKO mice neither increased the levels of ROS and RNS in skeletal muscle nor induced the expression and activation of the enzymes involved in the antioxidant response, 1 week following denervation.…”
Section: Discussionmentioning
confidence: 53%
“…The regional differences in mitochondrial function, either as a result of damage to the mitochondria by external mechanisms or regional impairment in function, may be attenuated by the presence of connections between mitochondria in subsarcolemmal and interfibrillar regions. 42, 43 …”
Section: Metabolism and Metabolic Flexibility In The Aging Heartmentioning
confidence: 99%
“…In the current study, we used SkQ1 antioxidant, based on the plastoquinone moiety linked to dodecyltriphenylphosphonium cation that targets SkQ1 to mitochondria [26]. SkQ1 and its analogs are efficient in the prevention of some age-associated pathologies, and they have therapeutic effects in animal models of diseases associated with inflammatory response (heart, brain, and kidney ischemic injury [27, 28], pyelonephritis [29], eye diseases [30, 31], sarcopenia [32], and dermal wound healing [33]). SkQ1 delays the development of various markers of aging and prolongs the lifespan of various animals [20, 22, 34, 35].…”
Section: Introductionmentioning
confidence: 99%